Performance in state tests for public accounting students in Colombia - Corredor García, María del Pilar; Trujillo Prada, Mariela Andrea; Villalba-Rodríguez, William Javier (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objective of the article, is to analyse the perception that public accounting students have about standardized test of the State, before their degree, it will allow in turn to establish if perception influences performance. The mixed methodology is used with a descriptive perspective, which was based on a documentary review on evaluation models, designing an instrument with a simple of 99 last grade participants. A reduction in scores compared to generic competencies is concluded; Reading comprehension, mathematics and English, which seeks continuous improvement from the research and training point of view.